Fenomena Fear of Missing Out (FoMO) dan Upaya Pemulihan Kesehatan Mental Siswa SMK di Kabupaten Buleleng Melalui Pendekatan Konseling Mindfulness: Sebuah Studi Fenomenologis - Ketut Manis Santi Purnami; I Wayan Lasmawan; Desak Putu Parmiti (SENTRI: Jurnal Riset Ilmiah, 2026)
The phenomenon of Fear of Missing Out (FoMO) is becoming increasingly prevalent among adolescents, particularly vocational high school (SMK) students in Buleleng Regency. Driven by the rapid expansion of social media and peer pressure, this condition is characterized by excessive anxiety and a compulsive need to remain digitally connected. FoMO significantly impacts mental health, triggering academic stress, sleep disturbances, and diminished self-esteem. This study aims to describe students' subjective experiences of FoMO, analyze its psychological consequences, and explore the effectiveness of mindfulness-based counseling as a recovery strategy. Methods: This qualitative phenomenological study involved SMK students in Buleleng exhibiting FoMO symptoms. Data were collected through in-depth interviews, observations, and documentation, then analyzed using data reduction, thematic categorization, and phenomenological interpretation to capture the deepest essence of the participants lived experiences. Findings: The results reveal that students perceive FoMO as a "digital prison" that creates social anxiety and constant pressure to conform to trends. However, during the recovery phase through mindfulness-based counseling, a profound subjective transformation was discovered: students shifted from a feeling of being "alienated within digital crowds" toward self-reclamation. Informants described the recovery experience as a "breath of fresh air," where they were able to release their impulsive attachment to devices. The essence of this recovery is marked by the emergence of presence, where students feel more "whole" and sovereign over their own emotions, no longer tethered to external validation or digital notifications. This study affirms that FoMO is a genuine threat to adolescent mental health. Mindfulness-based counseling proves effective as both a preventive and curative strategy, providing space for students to regain internal control. These findings contribute to strengthening school counseling services (BK) in navigating digital era challenges within the Indonesian context.